An expert judgement approach to determine measures to remove institutional barriers and economic non-market failures that restrict photovoltaic self-consumption deployment in Spain. (1st March 2019) - Rosales-Asensio, Enrique; de Simón-Martín, Miguel; Borge-Diez, David; Pérez-Hoyos, Ana; Comenar Santos, Antonio
Graphical abstract: Highlights: Solar PV and self-consumption have been halted in Spain due to several barriers. Un unstable regulatory framework for self-consumption influences its deployment. Strategies to accelerate high solar photovoltaic growth rates in Spain are proposed. Measures to promote PV integration in distribution may have a positive impact. Abstract: Despite the Spanish privileged geographical location and business leadership in the renewable energy field, currently is can be observed that the solar photovoltaic generation, electric self-consumption systems and net-metering policies deployment is much lower than it can be observed in other countries, even with lower energy sources for self-consumption. Energy policy experts assess as main reason the absence of a stable regulatory framework and the existence of clear disincentives. These disincentives are based on several economic non-market failures and institutional barriers. One key factor has proven to be the regulatory uncertainty created mainly by the recent national most relevant ministerial orders regarding energy generation and consumption, which suggests that, de facto, the regulatory framework is currently still under development. This paper includes first a brief but deep description of the prosumers penetration existing scenario in Spain, and then it focuses on feasible strategies to accelerate higher solar photovoltaic and self-consumption growth rates in Spain. Then, new policy measures to eliminate, or at least, mitigate, current barriers to their deployment are proposed and discussed. It is concluded that it results mandatory the urgent modernization of the energy regulatory framework promoting an active role for distributed PV generation which could have a significant positive impact in the voltage control and frequency regulation in distribution networks, among other advantages.